Learning outcomes of three teaching styles in collegiate volleyball classes - Zeng, H.; Liu, W.; Leung, R. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Of its eleven teaching styles in Mosston`s Spectrum of Teaching Styles (Mosston & Ashworth, 2001), Practice Style, Reciprocal Style, and Inclusion Style are the most frequently used. Practice Style is appropriate for average-level students and allows students to decide their own pace, frequency, repetition, and rest interval in practice. Reciprocal Style is valued for its social development because students practice in pairs and help each other. Inclusion Style provides multiple difficulty levels of skill tasks, so students can choose to practice at appropriate difficulty levels. While these three teaching styles are most frequently used in teaching motor skills, few studies were conducted investigating their effects on teaching motor skills. This study was designed to examine the effects of these three teaching styles on student learning outcomes (SLO) in collegiate volleyball classes. Methods Participants were 72 college students (27 girls and 45 boys) enrolled in physical education (volleyball) classes from a college in the US. Twenty-four students (9 girls and 15 boys) were randomly assigned to each of the three treatment groups. Each treatment followed its typical teaching and practice strategies outlined by Mosston and Ashworth (2001), and accepted a total of eight classes. A volleyball skill testing package (passing, spiking, and serving) developed by American Alliance for Health, Physical Education, Recreation and Dance (1991) was utilized to assess skill acquisitions after 8 volleyball classes. The scores on passing, spiking, and serving constituted a composite score, which represented the SLO. Statistical Analysis. The SLO was analyzed with a 2 (gender) × 3 (treatment conditions) factorial ANOVA. Independent variables were treatment conditions and gender, and the dependent variable was the SLO. Results A significant (p < .05) treatment-by-gender interaction was found for the SLO. Simple main effects tests yielded the following results. Males demonstrated significantly higher (p < .05) SLO than females in Practice Style group (males 90.58 ± .79 vs. females 75.50 ± .90). Females indicated significantly higher (p < .05) SLO than males in Inclusion Style group (females 88.17 ± 1.58 vs. males 73.74 ± 2.19) and in Reciprocal Style group (females 84.92 ± 1.56 vs. males 76.17 ± 2.25). Moreover, the Practice Style group obtained significantly higher (p < .05) SLO than the other two groups among males, and the Inclusion Style group got significantly higher (p < .05) SLO than the other two groups among females. Discussion / Conclusions Practice Style requires students to practice independently with their own decisions on pace, frequency, repetition, and rest interval. Compared with female students, male students are usually more independent and more task-oriented. When practicing with Practice Style, male students have clearer ideas regarding how to arrange their practice and are more likely to stick to tasks. In addition, male students have a better fitness level and are more tolerant to fatigue, and could use practice time more efficiently without many rest intervals in Practice Style. As a result, male students demonstrated best SLO with Practice Style. In contrast, female students are less independent and more social-oriented than male students, and need more feedback and rest intervals during practice. Thus, they may feel more comfortable with Reciprocal Style, which involves social interaction and immediate feedback from the partner. As for Inclusion Style, the teacher has designed multiple difficulty levels for students to choose, and female students can get task levels fitting their conditions best, resulting in a better SLO. As a result, females indicated better SLO than males in Reciprocal Style and Inclusion Style, and demonstrated best SLO in Inclusion Style. Further research is needed to confirm the results of the present study.